A Promising Approach for Decision Modeling With Single-Valued Neutrosophic Probabilistic Hesitant Fuzzy Dombi Operators - Kamran, Muhammad; Ashraf, Shahzaib; Naeem, Muhammad (Yugoslav Journal of Operations Research, 2023)
A combination of the single-valued neutrosophic set (SV-NS) and the probabilistic hesitant fuzzy set is the single-valued neutrosophic probabilistic hesitant fuzzy (SV-NPHF) environment (PHFS). It is intended for some unsatisfactory, ambiguous, and contradictory circumstances in which each element has a number of various values that are brought about by the situation’s actuality. The decision-maker can quickly gather and analyze the facts by employing a strategic decision-making technique. On the other hand, uncertainty will be a big part of our daily lives when we are learning. We present a decision-making strategy for the SV-NPHF context to address this data ambiguity. The fundamental operational concepts for SV-NPHF information under Dombi aggregation operators were initially developed on the basis of this study. The SV-NPHF Dombi weighted arithmetic average (SV-NPHFDWAA) operator and SV-NPHF Dombi weighted arithmetic geometric (SV-NPHFDWAG) operators are two SV-NPHF Dombi aggregation Operators that are then examined. Following that, we look into further characterizations of the proposed operators, including idempotency, boundedness, and monotonicity. For the derived operators, we additionally developed the score and accuracy functions. When using SV-NPHF data in a multi attribute decision support system (MADSS), it is necessary to compare the effectiveness of various (AOs) in order to make the best decision. In addition, it is demonstrated how to use symmetry analysis to choose the optimal social media platform for earning and learning in a practical application of SV-NPHFDWAA and SV-NPHFDWAG.